Indicator models of real GDP growth in the major OECD economies - Pain, Nigel (OECD Publishing, 2006)
Accurate and timely information on the current state of economic activity is an important requirement for the policymaking process. Delays in the publication of official statistics mean that a complete picture of economic developments within a particular period emerges only some time after that period has elapsed. Thus considerable resources are, at times, devoted to making an assessment of the immediate past and the current conjuncture as well as projections about future developments. In practice, a regular flow of information is provided by the large number of quantitative and qualitative indicators that appear each month for different sectors of the economy. One challenge for policymakers is to put these together in a consistent manner to obtain a picture of the overall state of the economy
Keywords: Economics